Mahatma Gandhi: A Practical Activist of Environmental Sustainability in Early 20th Century India - Ulfat Sadiqa (Al Manhal Research Journal, 2023)
Mahātmā Gandhi is often known as a political activist, a social reformer, a religious scholar, a creative author, and a prominent thinker of the Subcontinent in 20th century. In the observation of many scholars Gandhi was an apostle of applied human ecology. He was considered as the pioneer of the emergence of the modern environmental movements in India. The concept of environmental degradation, conservation, protection, sustainability, and survival, on which modern environmentalists are embarking upon, were inherent in the ideology of Gandhi. He was a man far ahead of his time and all the modern ecologists. In this regard, this paper describes the ideology and ethical approaches of Gandhi for sustainability of natural resources. Through discussing Gandhi’s practice of non-violence and supreme humanism, this article inspires human beings to minimize their destructive scheme in the name of development. The descriptive and analytical method is applied to identify the aims, approaches, ecological contributions, and conservational practices of Gandhi. The conclusion reveals the fact that Gandhi was indeed the role model in ecological paradigm and his practices of ahimsa and philosophy of self-realization proved the possibility of satisfactory coexistence of other living beings with humans. Thus, his philosophy of bio-spherical egalitarianism is relevant to eradicate the environmental crises of 21st century.